2014
DOI: 10.1021/jo502213t
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Fluorophores with Large Stokes Shifts: 9-Iminopyronin Analogues as Clickable Tags

Abstract: The design, synthesis, and both experimental and theoretical studies of several novel 9-(acylimino)- and 9-(sulfonylimino)pyronin derivatives containing either an oxygen or a silicon atom at position 10 are reported. These compounds, especially the Si analogues, exhibit remarkably large Stokes shifts (around 200 nm) while still possessing a high fluorophore brightness, absorption bands in the near-UV and visible part of the spectrum, and high thermal and photochemical stabilities in protic solvents. The reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 70 publications
5
94
0
3
Order By: Relevance
“…As shown in Figure 3c,h igh Stokes shift values (117, 104, 159, and 125 nm, respectively)f or all dyes might be attributed to the ICT excitation of an electron from the HOMOt ot he LUMO of the sensitizer. [39] Time-dependent (TD) DFT calculations were carried out to analyze the photophysical behavior of these complexes and to understand the transitionsi nt erms of the molecular orbitals in DMF at the CAM-B3LYP/6-311G(d,p) level of theory. Then ormalized simulated and experimental UV/Vis spectra of MCG1-MCG4 are given in Figure S3 in the Supporting Information.T he spectra were produced by deconvoluting Gaussian functions with af ull-width at half-maximum (FWHM) of 0.37 eV centered at the excitation wavenumbers.…”
Section: Photophysical Characterizationmentioning
confidence: 99%
“…As shown in Figure 3c,h igh Stokes shift values (117, 104, 159, and 125 nm, respectively)f or all dyes might be attributed to the ICT excitation of an electron from the HOMOt ot he LUMO of the sensitizer. [39] Time-dependent (TD) DFT calculations were carried out to analyze the photophysical behavior of these complexes and to understand the transitionsi nt erms of the molecular orbitals in DMF at the CAM-B3LYP/6-311G(d,p) level of theory. Then ormalized simulated and experimental UV/Vis spectra of MCG1-MCG4 are given in Figure S3 in the Supporting Information.T he spectra were produced by deconvoluting Gaussian functions with af ull-width at half-maximum (FWHM) of 0.37 eV centered at the excitation wavenumbers.…”
Section: Photophysical Characterizationmentioning
confidence: 99%
“…The results of qPCR showed that the oligo nucleotide probes with TMB can be applied in qPCR experiments on a par with hydrophilic fluorescent labels, such as FAM. TaqMan type fluorescent probes were prepared by conjugation of the alkyne substituted dye (com pound (2) or FAM alkyne (N (prop 2 yn 1 yl) 5 carboxamide fluorescein, Lumiprobe, United States)) with the azide containing oligonucleotide (Syntol, Russia) using the Cu(I) TBTA catalyst (Lumiprobe, United States) according to manufac turer's procedure. Probes were purified by HPLC on a C4 reversed phase column (Phenomenex) equili brated with 100 mM ammonium acetate in the aceto nitrile gradient (from 8 to 60% of acetonitrile per 40 min); the flow rate was 0.7 mL/min.…”
Section: Preparation and Application Of A Bodipy Labeledmentioning
confidence: 99%
“…In the present work, the fluorescent probes for qPCR were obtained by the scheme where an alkyne containing fluorophore is attached to an oligonucleotide with a fluorescence quencher at one end and the azide group at another end by the click reaction. This approach expands the choice of fluorophores by a set of alkyne derivatives of dyes, which are commercially available or can be synthesized easily [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Molecules with small Stokes shift generally suffer from self‐quenching . Therefore, large Stokes shift is an important aspect to diminish reabsorption and light scattering in optical materials, such as fluorescent probes,, organic lasers, and quantum dots .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, large Stokes shift is an important aspect to diminish reabsorption and light scattering in optical materials, such as fluorescent probes,, organic lasers, and quantum dots . The enhanced Stokes shift can be achieved by excited‐state geometry relaxation accompanied by solvent reorganization ,. Consequently, efforts were taken for the creation of functionalized imidazo[1, 5a]pyridine derivatives with a large Stokes shift to achieve the fine‐tuned photophysical properties.…”
Section: Introductionmentioning
confidence: 99%